SOME ACTUAL PROBLEMSIN DIAGNOSTIC, CLASSIFICATION AND PSYCHOPATHOLOGY OF SCHIZOPHRENIA - Винник, М. І.; Бежук, Ю. М.; Ромаш, І. Р.; Бондар, О. М.; Краснопольська, І. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Thiswork, based on the analysis of world literature, provides data about the most important issues of classification, etiology and pathogenesis, diagnostic and clinical manifestations of schizophrenia. Shown that none of these issues has unambiguous interpretation today.